# Newton's Law of Cooling

*Newton's Law of Cooling* states that the temperature of a body changes at a rate proportional to the difference in temperature between its own temperature and the temperature of its surroundings.

We can therefore write

where,

T = temperature of the body at any time, t

T_{s} = temperature of the surroundings (also called ambient temperature)

T_{o} = initial temperature of the body

k = constant of proportionality

$\dfrac{dT}{dt} = -k(T - T_s)$

$\dfrac{dT}{T - T_s} = -k \, dt$

$\ln (T - T_s) = -kt + \ln C$

$\ln (T - T_s) = \ln e^{-kt} + \ln C$

$\ln (T - T_o) = \ln Ce^{-kt}$

$T - T_s = Ce^{-kt}$

when t = 0, T = T_{o}

$C = T_o - T_s$

Thus,

$T - T_s = (T_o - T_s)e^{-kt}$

The formula above need not be memorized, it is more useful if you understand how we arrive to the formula.

- Add new comment
- 61652 reads